Interlocuções entre a meritocracia e o coaching: uma relação das análises de poder - Silva, Amanda Borba Ramos (2021)
This research seeks to present the theme of meritocracy, considering its theoretical-conceptual aspects with regard to social, economic, historical and cultural reverberations, which are addressed by bibliographical references that discuss the phenomenon. In order to understand meritocratic discourse and practices, FEBRACIS was chosen to observe how a coaching institution, which declares itself meritocratic, promotes it socially and has publicly accessible materials. For this, as a methodology, we opted for document analysis and thematic analysis as a methodological tool associated with document analysis, to deepen the materials, these two books, "The power of action" (Vieira, 2015) and "The power of self-responsibility” (Vieira, 2017a), as well as the institution website, sources that made it possible to deepen the objective. The chosen materials address, in an accessible and broad way, the techniques, tools and concepts of the CIS method, institutional modeling proposal and the concept of self-responsibility, which is closer to meritocracy. From these materials, after applying the methods, results were extracted that indicated that there was, in institutional discourses and practices, a set of techniques, tools and concepts aimed at building a specific individual, the super-human, possible from the journey of human progress, which encompasses the CIS method. However, the results showed the relevance exerted by the creator of the method and company’s president. Thus, the discussion analyzed company’s president role in the institution, the relevance of religion and science in institutional discourses and practices and in the CIS method, as well as the journey of human progress and its four stages (awareness, self-responsibility, positive vision of the future and the powerful tools of progress). For the discussion, Michel Foucault's concepts were used in order to problematize the highlighted points, considering their disciplining function. Finally, it is concluded that there was a contribution to studies on meritocracy and that it was possible to observe how the practices and discourses of the CIS method, the institution cooperate for the constitution of a successful individual through training, from the docilization of useful bodies, turning to productivity and competitiveness.